“DEVELOPING CREATIVE THINKING AND AESTHETIC SENSIBILITY IN SCHOOL-AGE CHILDREN THROUGH FOLK APPLIED ARTS” - Raxmonova Rayxon Zoir qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores the role of folk applied arts in developing creative thinking and aesthetic sensibility in school-age children. The study examines children’s activities in creating patterns and ornaments, combining colors and shapes, and presenting and sharing their work. The results indicate that folk applied arts enhance children’s respect for national culture, foster creative thinking, and develop aesthetic perception. Furthermore, integrating folk arts into the educational process serves as an effective tool for cultivating cultural literacy in children.